Evaluation of successful treatment of patients with unilateral functional crossbite: Ovrednotenje uspešnega zdravljenja pacientov z enostranskim funkcionalnim križnim grizom - Fekonja, Anita; Šijanec Kebrič, Jasmina (Acta Medico-Biotechnica, 2022)
Purpose: Unilateral functional crossbite (UFCB) is one of the most common malocclusions in the deciduous and early mixed dentition stage. It is accompanied by lateral mandibular shift and mandibular midline deviation due to the narrow maxillary dental arch. The aim of this study was to assess the effects of early correction of UFCB with the Fränkel (FR–3) functional regulator. Methods: Ninety Caucasian subjects (32 boys and 58 girls) with UFCB in the early mixed dentition stage (mean age, 6 years and 8 months (SD±1.8)) were treated with the FR–3 functional regulator and monitored. The diagnosis was based on anamnestic data, clinical examinations, radiographs, and analyses of study cast models. Dental casts taken before and after treatment were used in the analysis of effects. Results: Treatment of UFCB involved expansion of the maxillary arch, removal of occlusal interferences, and elimination of the functional shift. The width of the maxilla increased by 2.90 mm (SD±1.63) in the canine region and by 2.78 mm (SD±1.60) in the molar region. Another advantage of early treatment was improvement of maxillary arch length deficiency secondary to maxillary constriction because the permanent incisors were afforded more space before or during eruption than if the crossbite was treated at a later age. At least one abnormal orofacial function was identified in 69 (76,67%) patients with UFCB. After treatment, all crossbites were corrected, functional deviations were eliminated, and no relapses were observed during follow–up at 2 years and 8 months. Conclusion: The Fränkel functional regulator is a functional orthodontic–orthopedic device that is an effective alternative for the treatment of UFCB. Dental occlusion was significantly improved, and the prognosis for normal craniofacial growth and normal function of the stomatognathic system was enhanced.